Seleção entre e dentro de progênies de erva-mate para o enraizamento adventício - Gazzana, Denise (2019)
The objective of this work was to evaluate half-sib progenies of mate (Ilex paraguariensis A. St.-Hil.) and develop selection strategies for vegetative propagation by mini-cuttings. Genotypes of six mate progenies (17SM1, 17SM3, 17SM4, 17SM7, 17SMLZ and 17SMJS) were selected for morphological traits. Seedlings were established in a clonal mini-garden in the closed soilless cultivation system inside an acclimatized greenhouse. Seedlings of each progeny were planted in one line spaced 10 x 10 cm and fertigated with nutrient solution. A drastic pruning was done to stimulate the growth of lateral shoots. For adventitious rooting, sprouts were sectioned in single-bud mini-cuttings of about 2 cm in length and one leaf with 50% of the original area. Four consecutive collections of shoots were done in periods ranging from 75 to 120 days, according to the availability of propagation material. Number of minicuttings per mini-stump was recorded in each collection. The mini-cuttings were treated with a hydro alcoholic solution (1: 1 v / v) of 2000 mg L-1 of indolbutyric acid. Polyethylene trays with 100 wells were filled up with the same proportions of commercial pinus-bark substrate, medium vermiculite and coarse sand, planted the mini-cuttings and placed in a humid chamber. At 60 days of cultivation, mini-cuttings were evaluated for the percentages of survival and rooting of mini-cuttings, number of roots, average length of the three largest roots and number of rooted mini-cuttings. Pearson's linear correlations were estimated among traits. Estimation of variance components and prediction of the genetic gain were run with the REML/BLUP procedure of SELEGEN. The number of rooted mini-cuttings showed positive and significant correlations with number of mini-cuttings per mini-stump, percentages of survival and rooting of mini-cuttings, number of roots and average length of the three largest roots. The number of roots and number of rooted mini-cuttings showed the highest heritability estimations, allowing high genetic gain from selection. The identification of the best genotypes was done based upon the number of rooted mini-cuttings and the predicted genotypic components with greater direct and indirect selection gain. Selection for adventitious rooting based upon the number of rooted mini-cuttings can be used in mate breeding programs for vegetative propagation by mini-cuttings. Genotypes with high adventitious rooting competence can be selected from different mate progenies.